Service based comparison of group cognitive behavior therapy to waiting list control for chronic fatigue syndrome with regard to symptom reduction and positive psychological dimensions. Issue 39 (September 2019) - Heald, Adrian; Barber, Louise; Jones, Helen Lyon; Farman, Sanam; Walther, Andreas
Abstract: Background: Although chronic fatigue syndrome (CFS) sometimes referred to as myalgic encephalomyelitis (ME) is a very challenging condition to treat, there is evidence that individual cognitive behavioral therapy (ICBT) can be effective for treatment and management of its symptoms. Furthermore, group cognitive behavioral therapy (GCBT) is emerging as promising treatment for the condition. The aim of the present study was to explore further the effectiveness of GCBT in a routine clinical setting and to investigate associated positive psychological effects related to GCBT. Methods: In this pragmatic, non-randomized, controlled trial, 28 people acted as their own waiting list control by completing a range of measures 8 weeks prior to taking part in the GCBT. The intervention consisted of 8 consecutive weeks of 2.5-hour sessions. Results: Repeated measures analysis of covariance revealed significant improvements in physical fatigue ( F = 28.31, P < .01, effect size d = 0.52), mental fatigue ( F = 7.72, P < .01, effect size d = 0.22), and depressive symptoms (Beck depression inventory-fast screen for medical individuals [BDI-FS]: F = 11.43, P < .01, effect size d = 0.30; hospital anxiety and depression scale [HADS-D]: F = 16.72, P < .01, effect size d = 0.38) compared with the waiting list. Improvements in quality of life ( F = 7.56, P < .01, effect size d = 0.23), hope ( F = 15.15, P < .01, effect size d = 0.36), and optimism ( F = 8.17, P < .01, effect size d = 0.23) were also identified, but no change was reported for anxiety levels. Global outcome measures revealed that the majority of the individuals found the treatment beneficial and were satisfied with the results. Conclusion: GCBT is a beneficial and cost-effective treatment that individuals find amenable in routine clinical practice for CFS. Additionally we have described important effects emerged on positive psychological dimensions such as hope and optimism potentially enhancing the overall benefit.